TECHNICAL SKILLS AND THE ACADEMIC PERFORMANCE OF GRADE 9 TECHNOLOGY AND LIVELIHOOD EDUCATION STUDENTS: A BASIS FOR PLACEMENT PLAN - Agluba, Christian Anthony (International Journal of Arts, Sciences and Education, 2021)
This research examined the academic performance of Grade 9 Technology and Livelihood Education students in order to create a placement strategy for incoming Grade 10 students. It also revealed the pupils' interests in various technical-vocational and academic fields. The research included 240 Talavera National High School SY-2018-2019 Grade 9 students from the third grading session. The 240 students were split into four groups: Agriculture, Cookery, SMAW, and ICT. The data were analyzed using descriptive statistics like mean, percentage, and standard deviation, as well as inferential statistics like Pearson's r. The majority of responders were 14-year-old males with an average grade of 85-89 in the first and second grading periods. In terms of interest in Tech-Voc and Academic strands, students with specialty in Agriculture exhibited the most interest in GAS, followed by students with specialization in Cookery, SMAW, and STEM with specialization in ICT. Overall, students preferred Academic streams and were more likely to enroll in them in Senior High School. All groups have excellent technical abilities. This indicated that pupils in Grade 9 had sufficient understanding in their field. Specifically, a negative connection was observed between technical competence and interest in agriculture among responders specializing in Agriculture and Cookery. Technical ability and interest in HUMSS and STEM were strongly correlated for students studying ICT. Students taking Cookery, SMAW, and ICT technical competence had a significant favorable connection with academic achievement. Cookery, SMAW, and ICT technical abilities were high among responders with good academic achievement. Getting Tech-Voc strands should be prioritized since it improves kids' academic achievement. Instructors, especially TLE and Tech-Voc teachers, must encourage pupils to continue their specialty in Senior High School. This manner, kids may develop their technical skills and be more successful in school and in life.